On Adjustment Costs and the Stability of Equilibria - Macleod, W. Bentley (Review of Economic Studies, 1985)
In practice one does not expect conflicting agents to move instantaneously to an equilibrium. Instead the final equilibrium is often the consequence of "disequilibrium dynamics". This paper, through the use of local game theory, introduces a general framework for disequilibrium dynamics based on the existence of adjustment costs. The analysis is presented within the context of oligopoly theory and shows that the existence of adjustment costs will in many cases result in a unique equilibrium at which market shares are inversely proportional to these costs. This paper also introduces two new solution concepts for n-person normal form games.